Pengaruh Biaya Distribusi terhadap Peningkatan Volume Penjualan: Studi Kasus pada Perusahaan Industri Manufaktur Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Maria Octavia Gale; Henrikus Herdi; Pipiet Niken Aurelia (Jurnal Akuntan Publik, 2024)
This study aims to determine the effect of distribution costs on increasing sales volume in food and beverage sector manufacturing industry companies listed on the IDX in 2020-2022. This research uses quantitative methods, this research was carried out on Food and Beverage Sector Manufacturing Industry Companies Listed on the IDX, and data taken for three years starting from 2020-2022 and the calculation uses data per semester consisting of Distribution Costs and Sales Volume. Data collection is carried out by documentation method. The population in this study is all Financial Statements of Food Sector Manufacturing Companies and Minimums Listed on the IDX from 2020-2022 totaling 78 Financial Statements Where the sample processed is part of the total population in the Income Financial Statements per semester in the 2020-2022 period which amounts to 24 Income Financial Statements. The data analysis carried out was by descriptive statistics and simple linear regression analysis while for significant testing using the t test. The results showed that: Distribution costs have a significant effect on sales volume in Food and Beverage Sector Manufacturing Industry Companies Listed on the IDX.